Surgical correction of polymelia in the perineal region of a 2-day-old indigenous bovine calf: a case report from Bangladesh - Munif, Mohammad Raguib (2023)
Polymelia is an occasional and congenital malformation in bovine calves, characterized by the presence of single or multiple accessory limb(s) at various body regions, which are often called the supernumerary limb(s). One of these defects is known as pygomelia, where the additional limb is attached to the pelvis within the perineal region. This study describes such a case along with surgical management.